Significance of TNF-α and the Adhesion Molecules: L-Selectin and VCAM-1 in Papillary Thyroid Carcinoma - Kobawala, Toral P. (J Thyroid Res, 2016)
Circulating levels of TNF-α and the adhesion molecules L-Selectin and VCAM-1 as well as their expression in the primary tumors of patients with benign thyroid diseases and papillary thyroid carcinoma (PTC) have been determined in this study. The serum levels of TNF-α, L-Selectin, and VCAM-1 were significantly higher in patients with both benign thyroid diseases and PTC as compared to the healthy individuals. However, the levels of only TNF-α and L-Selectin, and not VCAM-1, were significantly higher in patients with PTC in comparison to those observed in patients with benign thyroid diseases. Further the expression of TNF-α and L-Selectin was also significantly higher in the primary tumors of PTC patients, relative to the benign thyroid diseases. The expression of L-Selectin and VCAM-1 significantly correlated with aggressive tumor behavior. In PTC patients, the circulating TNF-α levels significantly positively correlated with the levels of L-Selectin, while TNF-α immunoreactivity was significantly associated with VCAM-1 expression. Serum TNF-α was found to be a significant prognosticator for OS in PTC patients. Overall the results signify that the interaction between TNF-α and the adhesion molecules may have a role in thyroid carcinogenesis and understanding this complexity may offer potential therapeutic targets for better management of thyroid cancer.